Auditory steady‐state response at 20 Hz and 40 Hz in young typically developing children and children with autism spectrum disorder. Issue 6 (24th April 2020) - Ono, Yasuki; Kudoh, Kiwamu; Ikeda, Takashi; Takahashi, Tetsuya; Yoshimura, Yuko; Minabe, Yoshio; Kikuchi, Mitsuru
Abstract : Aim: The early detection of autistic tendencies in children is essential for providing proper care and education. The auditory steady‐state response (ASSR) provides a passive, non‐invasive technique for assessing neural synchrony at specific response frequencies in many mental disorders, including autism spectrum disorder (ASD), but few studies have investigated its use in young children. This study investigated the ASSR at 20 Hz and 40 Hz in typically developing (TD) children and children with ASD aged 5–7 years. Methods: The participants were 23 children with ASD and 32 TD children aged 5–7 years. Using a custom‐made magnetoencephalography device, we measured ASSR at 20 Hz and 40 Hz, compared the results between groups, and evaluated the association with intellectual function as measured by Kaufmann Assessment Battery for Children. Results: Responses to 20 Hz and 40 Hz were clearly detected in both groups with no significant difference identified. Consistent with previous findings, right dominance of the 40‐Hz ASSR was observed in both groups. In the TD children, the right‐side 40‐Hz ASSR was correlated with age. The Kaufmann Assessment Battery for Children score was correlated with the left‐side 40‐Hz ASSR in both groups. Conclusion: Right‐dominant ASSR was successfully detected in young TD children and children with ASD. No difference in ASSR was observed between the children with ASD and the TD children, although the right‐side 40‐Hz ASSR increased with age only in the TD children. Left‐side 40‐Hz ASSR was associated with intelligence score in both groups.